DESCRIPTIVE STUDY OF ACADEMIC STRESS IN UNP PSYCHOLOGY STUDENTS - Amalina, Dinda Rizky; Fadila Annisa; Nurhabibah; Patricia Viona Evelin; Silfi Erisa Hestari (In Trend : International Journal of Trends in Global Psychological Science and Education, 2024)
Academic stress is a type of stress that originates from the demands of academic activities or the learning process. This stress is perceived by students as a burden that exceeds the limits of ability, which is characterized by various reactions that affect physical, emotional and behavioral aspects. Academic stress affects psychological states, including emotional, cognitive, and behavioral factors that can contribute to illness. This research aims to determine the level of academic stress in psychology students at Padang State University. The research design used was descriptive analytical. The sampling technique used in this research was simple random sampling. The method in this research is to use descriptive qualitative research methods. The population of this research is Padang State University students, while the sample of this research is Padang State University Psychology students. The instrument in this research uses an academic stress questionnaire which is based on 4 aspects according to Robotham (2008), consisting of cognitive, affective, physiological and behavioral aspects. Based on research that has been conducted with the population of this study, namely Padang State University students, while the sample from this research is Padang State University Psychology students. Of the 48 respondents who participated, it was found that 6 respondents were at a low stress level with a percentage of 12.5%, and 37 respondents were at a moderate stress level with a percentage of 77.08%, then 5 respondents were at a high stress level. with a percentage of 10.4%. Based on research conducted on 48 respondents who were psychology students at Padang State University, it was found that the majority of academic stress was at a moderate stress level.